2017
DOI: 10.1371/journal.pone.0187227
|View full text |Cite
|
Sign up to set email alerts
|

Do intra-articular hyaluronic acid injections delay total knee replacement in patients with osteoarthritis – A Cox model analysis

Abstract: Due to the growing worldwide prevalence of knee osteoarthritis, the optimal management of this issue is critical for reducing its burden.ObjectivesThis study aimed to describe patients treated for knee osteoarthritis between 2006 and 2013 in France and to compare the delay from diagnosis to total knee replacement between patients who received intra-articular hyaluronic acid injections and those who did not receive the injections. A second objective was to compare direct medical costs for ambulatory care betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 55 publications
4
39
0
3
Order By: Relevance
“…Our data are also consistent with studies of large‐claim databases that showed a delay in knee arthroplasty associated with HA injection . Given that these studies did not distinguish between the methods of HA injection (US versus landmark guided), it is likely that greater delays to surgery may have been observed in the subset of patients receiving US‐guided HA.…”
Section: Discussionsupporting
confidence: 86%
“…Our data are also consistent with studies of large‐claim databases that showed a delay in knee arthroplasty associated with HA injection . Given that these studies did not distinguish between the methods of HA injection (US versus landmark guided), it is likely that greater delays to surgery may have been observed in the subset of patients receiving US‐guided HA.…”
Section: Discussionsupporting
confidence: 86%
“…The most representative injection was hyaluronic acid (HA) or corticosteroid which has been approved by United States Food and Drug Administration (US FDA) and European Medicines Agency (EMA) for the treatment of knee osteoarthritis (KOA). The clinical practice confirmed that the therapy can reduce joint pain and improve joint function, reduce the dosage of non-steroidal antiinflammatory drugs (NSAIDs) and delay the total knee replacement [3][4][5][6][7]. However, there are also problems such as short duration of curative effect, increased cost, and inappropriate use of patients in advanced stage and increased risk of infection in multiple articular cavities [8][9][10][11].…”
Section: Discussionmentioning
confidence: 97%
“…Multiple courses of IAHA can cause long-term beneficial outcomes, including reduction in analgesics used and delay in the need for joint replacement surgeries [19] still found regarding the risk benefit of IAHA. However, controversy about lack of agreement among international guidelines regarding the use of IAHA for the management of symptomatic knee OA still exists [20].…”
Section: Hydroxychloroquinementioning
confidence: 99%